Pengelolaan Kelas Program Khusus Layanan Pendidikan Cerdas Istimewa (Studi Kasus Di MTs Negeri 1 Wonogiri) - Parmanto, Parmanto, Dr. Eko Supriyanto, S.H, M.H, Dr. Darsinah, M.Si (2015)
Parmanto. Q.100 130 059. Specific Program Classes Management on Special Smart Education Services (A Case Study at State MTs 1 Wonogiri). Muhammadiyah University of Surakarta. 2015. The purpose of this study: (1) to discribe the planning specific program classes on special smart education services services at State MTs 1 Wonogiri, (2) to discribe the implementation specific program classes on special smart education services at State MTs 1 Wonogiri, (3) to discribe the evaluation specific program classes on special smart education services at State MTs 1 Wonogiri. The location of the research at State MTs 1 Wonogiri. This reaserch Led a qualitative reaserch with na approach etnography. Technic of collecting data in this study using an Conservation, depth interview, an document analysis methods. Model of data analysis in this study using data analysis organized for description. The result of this study are (1) planning specific program classes on special smart education services at State MTs 1 Wonogiri started with SWOT analysis they are has met the terms and conditions of the existing theory so that it can run properly; (2) implementation specific program classes on special smart education services at State MTs 1 Wonogiri covers six aspects they are, the selection process of students, curriculum, and facilities and infrastruktur in general an appoinment of teachers, activities learning, and guidance and counseling services in generally do not meet the term and conditions of the existing theory so that has not run optimally; (3) evaluation specific program classes on special smart education services at State MTs 1 Wonogiri to assess the success of this program is evaluated continously at each in the end of teaching learning program. After held specific program classes in distric level, the number of student increased from year to year significanly.